Beyond crazy quilts : piecing, patchwork & embroidery for unique designs - Brown, Christen (Christen Joan) (C&T Publishing, 2025)
"Create beautiful, layered embroidery! Explore a unique collection of six block patterns featured in 12 creative projects that combine artwork with hand embroidery and embellishment stitches. This guide offers detailed instructions for pieced and crumbled patterns for strip, wedge, and crazy designs, including customized sashing, borders, and finishing techniques. Learn how to layer embroidery and embellishments on seam coverings, using a variety of stitches including thread, beads, and silk ribbon. With 155+ stitches, you'll also find tips for fabric shapes, seam lengths, and the perfect stitches to enhance your designs. Discover 155+ embroidery stitches and create 12 stunning projects, including wall hangings, table runners, and pillows, using traditional techniques, silk ribbon embroidery, beaded stitches, and more! Christen Brown fans will love the easy-to-follow patterns, piecing techniques, and embroidery tips for adding crazy flair to your embroidery and quilting projects. Explore endless creative possibilities with the first book dedicated to mastering beaded embroidery seams--your ultimate guide to adding dazzling detail to your projects."--Publisher.